Alfred Sohn-Rethel en littérature ou la violence de l’abstraction - Françoise Willmann (Recherches Germaniques)
Two novels published at the beginning of the 21st century, Don Juan de la Mancha, by Robert Menasse, and Rebellen, by Wolfgang Schorlau, bear both the imprint of Alfred Sohn-Rethel’s thought. This article addresses the way in which literary experience in those cases permits one to question the role of real abstraction at the heart of the commodity-form from an angle which is different from that of philosophical coherence of concepts. While real abstraction may be a fruitful tool in sciences, it’s also an instrument of bodily alienation.